2022
DOI: 10.1245/s10434-022-12385-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors After Pancreatectomy for Pancreatic Cancer Initially Metastatic to the Liver

Abstract: Background Resection of initially oligometastatic pancreatic ductal adenocarcinoma (PDAC) following response to first-line chemotherapy is controversial. We herein updated a previous case series to investigate the oncologic outcomes and preoperative factors that could drive the decision-making process. Methods This retrospective analysis was limited to patients with liver-only synchronous metastases who experienced complete regression of the metastatic component and und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The majority ( n = 69, 91%) of studies involved one metastatic site, while one study involved metastasis in multiple organs 82 and six studies did not report the number of organs involved. 41 , 45 , 50 , 51 , 53 , 84 Thirty (40%) studies encompassed synchronous metastasis, 29 , 31 , 33 , 34 , 40 , 42 , 43 , 44 , 46 , 47 , 48 , 49 , 51 , 52 , 56 , 60 , 61 , 64 , 69 , 70 , 72 , 73 , 75 , 80 , 83 , 88 , 89 , 90 , 91 , 92 whereas 21 (28%) involved metachronous metastases 13 , 27 , 35 , 37 , 53 , 57 , 58 , 59 , 63 , 65 , 67 , 71 , 74 , 76 , 77 , 79 , 93 , 94 , 95 , 96 and 16 (21%) studies involved both synchronous and metachronous metastases. 2 , 14 , 30 , 32 ...…”
Section: Resultsmentioning
confidence: 99%
“…The majority ( n = 69, 91%) of studies involved one metastatic site, while one study involved metastasis in multiple organs 82 and six studies did not report the number of organs involved. 41 , 45 , 50 , 51 , 53 , 84 Thirty (40%) studies encompassed synchronous metastasis, 29 , 31 , 33 , 34 , 40 , 42 , 43 , 44 , 46 , 47 , 48 , 49 , 51 , 52 , 56 , 60 , 61 , 64 , 69 , 70 , 72 , 73 , 75 , 80 , 83 , 88 , 89 , 90 , 91 , 92 whereas 21 (28%) involved metachronous metastases 13 , 27 , 35 , 37 , 53 , 57 , 58 , 59 , 63 , 65 , 67 , 71 , 74 , 76 , 77 , 79 , 93 , 94 , 95 , 96 and 16 (21%) studies involved both synchronous and metachronous metastases. 2 , 14 , 30 , 32 ...…”
Section: Resultsmentioning
confidence: 99%
“…Frigerio et al found that neutrophil-to-lymphocyte ratio <1.7 was significantly associated with improved overall survival and disease-free survival. 46 Bachellier et al identified that Ca19-9 <500 at diagnosis, R0 resection, and administration of adjuvant chemotherapy were independent prognostic factors for overall survival. 36 These factors are further discussed in subsequent sections.…”
Section: Liver Metastases In Pdacmentioning
confidence: 99%
“…Frigerio et al performed a retrospective analysis of 52 patients with liver-only synchronous metastasis, with 73.1% of patients having greater than two liver metastases. 46 All patients received preoperative chemotherapy (63.5% FOLFIRINOX, 36.5% gemcitabine-based) and had complete regression of metastatic lesions before surgical intervention on cross-sectional imaging. Of total patients, 67.3% had normalized Ca19-9 posttreatment.…”
Section: Liver Metastases In Pdacmentioning
confidence: 99%
See 2 more Smart Citations